Contribution of the CK2 Catalytic Isoforms α and α’ to the Glycolytic Phenotype of Tumor Cells - Zonta, Francesca (Cells, 2021)
CK2 is a Ser/Thr protein kinase overexpressed in many cancers. It is usually present in cells as a tetrameric enzyme, composed of two catalytic (α or α’) and two regulatory (β) subunits, but it is active also in its monomeric form, and the specific role of the different isoforms is largely unknown. CK2 phosphorylates several substrates related to the uncontrolled proliferation, motility, and survival of cancer cells. As a consequence, tumor cells are addicted to CK2, relying on its activity more than healthy cells for their life, and exploiting it for developing multiple oncological hallmarks. However, little is known about CK2 contribution to the metabolic rewiring of cancer cells. With this study we aimed at shedding some light on it, especially focusing on the CK2 role in the glycolytic onco-phenotype. By analyzing neuroblastoma and osteosarcoma cell lines depleted of either one (α) or the other (α’) CK2 catalytic subunit, we also aimed at disclosing possible pro-tumor functions which are specific of a CK2 isoform. Our results suggest that both CK2 α and α’ contribute to cell proliferation, survival and tumorigenicity. The analyzed metabolic features disclosed a role of CK2 in tumor metabolism, and suggest prominent functions for CK2 α isoform. Results were also confirmed by CK2 pharmacological inhibition. Overall, our study provides new information on the mechanism of cancer cells addiction to CK2 and on its isoform-specific functions, with fundamental implications for improving future therapeutic strategies based on CK2 targeting.